The Grasp Reflex and Moro Reflex in Infants: Hierarchy of Primitive Reflex Responses - Yasuyuki Futagi; Yasuhisa Toribe; Yasuhiro Suzuki (Hindawi Limited, 2012)
The plantar grasp reflex is of great clinical significance, especially in terms of the detection of spasticity. The palmar grasp reflex also has diagnostic significance. This grasp reflex of the hands and feet is mediated by a spinal reflex mechanism, which appears to be under the regulatory control of nonprimary motor areas through the spinal interneurons. This reflex in human infants can be regarded as a rudiment of phylogenetic function. The absence of the Moro reflex during the neonatal period and early infancy is highly diagnostic, indicating a variety of compromised conditions. The center of the reflex is probably in the lower region of the pons to the medulla. The phylogenetic meaning of the reflex remains unclear. However, the hierarchical interrelation among these primitive reflexes seems to be essential for the arboreal life of monkey newborns, and the possible role of the Moro reflex in these newborns was discussed in relation to the interrelationship.